Solar absorption thermal energy storage - Mohd. Senusi, Shahrullizam (2010)
In recent years, the global warming and environmental pollutions getting worse and create an awareness to the society to another alternative system which more environmental friendly such as application of solar energy in building cooling system. This thesis, described the simulation of the single stage solar absorption system that was developed by using water lithium bromide solution as refrigerant. The performance of the system will be analyzed based on different parameters. The parameters are evaporator, generator and condenser temperature. For higher evaporator and generator temperature, it will result a higher COP (coefficient of performance) of the system. However, a low condensing temperature will result a higher COP. For generator temperature from 60 to 80??, the absorption cycle at work efficiently. This simulation also will calculate to estimate cooling load, quantity of solar collector and size of thermal energy storage. Size of solar collector and thermal energy storage depends on cooling load required.